Taxing wages. 2010-2011. Special feature: trends in personal income tax and social security contribution schedules (Paris, 2012)
"Taxing Wages provides unique information on income tax paid by workers and on social security contributions levied upon employees and their employers in OECD countries. In addition, this annual publication specificies family benefits paid as cash transfers. Amounts of taxes and benefits are detailed programme by programme, for eight household types which differ by income level and household composition. Results reported include the marginal and effective tax burden for one- and two-earner families and total labour costs of employers.